The lovely function f has the beautiful property that, for each real number x :
f ( x ) + f ( x − 1 ) = x 2 .
If f ( 1 9 ) = 9 4 , what is f ( 9 4 ) ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Couldn't you evaluate the sum ∑ i = 2 0 9 4 ( − 1 ) i i 2 by expanding with difference of squares to get the equivalent arithmetic sequence sum ∑ i = 2 1 9 4 i + 2 0 2 − 9 4 ?
Log in to reply
Thanks, yes it is. I didn't know that. I am editing the solution.
Why did you add mod?
Log in to reply
The original question might have asked for the last three digits as answer.
Very nice solution
Might be a similar method.. but shorter.. f(18)=267, f(20)=306, f(22)=349.... a notable pattern is observed that of 35,39,43 (i.e. diff=4) .. therefore, for f(94) which is 37th term from f(20) we need to add 37/2(43X2+(36X4)) to the f(20) term.. therefore 306+4255=4561.. and ans =561. rather than number theory problem... better it be a functions + AP hope u liked it . :)
It is easy to verify that f ( 9 4 ) = 9 4 2 − 9 3 2 + ⋯ + 2 2 2 − 2 1 2 + 2 0 2 − 9 4 . Since a 2 − b 2 = ( a + b ) ( a − b ) we have f ( 9 4 ) = 9 4 + 9 3 + ⋯ + 2 2 + 2 1 + 2 0 2 − 9 4 = 2 9 4 ⋅ 9 5 − 2 2 0 ⋅ 2 1 + 2 0 2 − 9 4 = 4 5 6 1
Note that we have:
f(n) + f(n-1) = n^2, and f(n) + f(n+1) = (n+1)^2 = n^2 + 2n + 1 there for f(n+1) = f(n-1) + 2n + 1
We know f(19) = 94 =>
f(20) = 20^2 - 94 = 306
We know that f(22) = f(20) + 43, and so on which gives us an arithmetic progression with 37 terms with 43 as the first term and 43 + 4 * 36 as last term. We there get :
f(94) = f(20) + 37 (43+(43+4 36))/2 = 306 + 4255 = 4561
4561 mod 1000 = 561 hence the answer
(if any one would like to latex my solution, you are more than welcome.) Hope that my idea is explained sufficient.
Problem Loading...
Note Loading...
Set Loading...
The solution is edited due to contribution from Kevin Zhang (see his comments below) to shorten the solution:
Since f ( n ) = n 2 − f ( n − 1 ) and f ( 1 9 ) = 9 4 ⇒
f ( 2 0 ) f ( 2 1 ) f ( 2 2 ) f ( 9 4 ) = 2 0 2 − f ( 1 9 ) = 2 0 2 − 9 4 = 2 1 2 − 2 0 2 + 9 4 = 2 2 2 − 2 1 2 + 2 0 2 − 9 4 . . . = 9 4 2 − 9 3 2 + 9 2 2 − 9 1 2 + 9 0 2 − 8 9 2 + . . . + 2 2 2 − 2 1 2 + 2 0 2 − 9 4 = ( 9 4 − 9 3 ) ( 9 4 + 9 3 ) + ( 9 2 − 9 1 ) ( 9 2 + 9 1 ) + ( 9 0 − 8 9 ) ( 9 0 + 8 9 ) + . . . + ( 2 2 − 2 1 ) ( 2 2 + 2 1 ) + 2 0 2 − 9 4 = 9 4 + 9 3 + 9 2 + 9 1 + 9 0 + 8 9 + . . . + 2 2 + 2 1 + 2 0 2 − 9 4 = k = 2 1 ∑ 9 4 k + 2 0 2 − 9 4 = 4 2 5 5 + 4 0 0 − 9 4 = 4 5 6 1